Urban Activism in Eastern Europe and Eurasia. Strategies and Practices. - (:unkn) unknown (DOM publ., 2020)
Over recent decades, there has been a rise in the number of grassroots initiatives in urban spaces across Eastern Europe and Eurasia. A variety of groups and individuals are claiming the city space and its development and finding their own ways to initiate urban change. This book examines central questions about these activities. What are its main features in contemporary post-Soviet cities? What are the strategies and practices of an urban civic engagement that evolves both on a micro level and through larger-scale processes? The volume challenges the prevailing simplistic view of weak, passive, and scared citizens in Eastern European and Eurasian cities – places that are themselves often seen as shaped by neoliberal and authoritarian structures. Here, the editors argue for the vibrant diversity and dynamism in contemporary urban civic activism in Eurasia. Employing diverse sources such as photos, interviews with local activists, and scholarly reports from the fields of anthropology, planning, architecture, political sciences, and sociology, they explore the creativity and novelty of Eurasian grassroots activism. By drawing on these multi-disciplinary perspectives, they aim to overcome distances and initiate dialogues among the interested public, activists, urban decision makers, and academics in the East and West alike.
Keywords: Stadtsoziologie; Stadtgesellschaft; Urbanismus; Zivilgesellschaft; Aktivität; Bürgerinitiative; Bürgerbewegung; Internationaler Vergleich; Fotodokumentation; Interview; Analyse; Fallstudie; Städtevergleich; Recht auf Stadt